PERSPECTIVES ON WORK-HOUR RESTRICTIONS AMONG GENERAL SURGERY RESIDENTS - Dr. M. Viswa Bhushana Raghuveer (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
The researchers were keen to learn what general surgery physicians think about the idea of restricted work hours. The survey examined what residents think about the effects an 80-hour workweek might have on how long it takes to train, gain surgical experience, get an education and on total well-being. Responses from senior and junior residents were compared by using Fisher’s method. The survey results include 158 replies from 360 residents in the community: 70 from seniors and 88 from juniors. A large portion, 79%, said they worked between 75 and 100 hours each week. A lower percentage of juniors (43%) believed reducing work would reduce their chance to perform surgery than did senior residents (74%) (p < 0.001). A majority from both groups thought cutting work hours would make their lives better (86% vs. 96%, p = 0.12). Most residents, at 60%, said they did not expect longer training because of the new rules. About half of juniors thought that 24-hour shifts were bad for their health, but only a quarter of seniors agreed (p = 0.001). Still, both sides agreed that removing overnight surgery could decrease surgeons’ risk of exposure (84% vs. 70%). Fewer than one-third of people in the area backed the idea to no longer have emergency care available around the clock. In addition, 47% (41% of seniors, 51% of juniors, p = 0.26) expressed agreement with the suggestion of working 80 hours weekly. Senior general surgery residents in Canada see the rules about work hours differently than junior residents. Even though some believe in limiting workweeks, neither group is really in favor of the 80-hour workweek or bringing back 24-hour call.